OsKEAP1 Interacts with OsABI5 and Its Downregulation Increases the Transcription of OsABI5 and the ABA Response Genes in Germinating Rice Seeds - Liu, Yan-Hua (Plants (Basel), 2021)
Kelch-like ECH-associated protein 1 (KEAP1)–nuclear factor E2-related factor 2 (NRF2) is the key antioxidant system in animals. In a previous study, we identified a probable KEAP1 ortholog in rice, OsKEAP1, and demonstrated that the downregulation of OsKEAP1 could alter the redox system and impair plant growth, as well as increase the susceptibility to abscisic acid (ABA) in seed germination. However, no NRF2 orthologs have been identified in plants and the mechanism underlying the phenotype changes of downregulated oskeap1 mutants is yet unknown. An in silico search showed that OsABI5 is the gene that encodes a protein with the highest amino acid identity score (38.78%) to NRF2 in rice. In this study, we demonstrated that, via yeast two-hybrids analysis and bimolecular fluorescence complementation assays, OsKEAP1 interacted with OsABI5 via its Kelch repeat domain in the nucleus. In germinating seeds, the expression of OsKEAP1 was significantly downregulated in oskeap1-1 (39.5% that of the wild-type (WT)) and oskeap1-2 (64.5% that of WT), while the expression of OsABI5 was significantly increased only in oskeap1-1 (247.4% that of WT) but not in oskeap1-2 (104.8% that of WT). ABA (0.5 μM) treatment significantly increased the expression of OsKEAP1 and OsABI5 in both the oskeap1 mutants and WT, and 4 days post treatment, the transcription level of OsABI5 became significantly greater in oskeap1-1 (+87.2%) and oskeap1-2 (+55.0%) than that in the WT. The ABA-responsive genes (OsRab16A and three late embryogenesis abundant genes), which are known to be activated by OsABI5, became more responsive to ABA in both oskeap1 mutants than in the WT. The transcript abundances of genes that regulate OsABI5, e.g., OsSnRK2 (encodes a kinase that activates OsABI5), OsABI1, and OsABI2 (both encode proteins binding to OsSnRK2 and are involved in ABA signaling) were not significantly different between the two oskeap1 mutants and the WT. These results demonstrated that OsKEAP1 played a role in the ABA response in rice seed germination via regulating OsABI5, which is the key player in the ABA response. In-depth analyses of the components and their action mode of the KEAP1–NRF2 and ABA signaling pathways suggested that OsKEAP1 likely formed a complex with OsABI5 and OsKEG, and OsABI5 was ubiquitinated by OsKEG and subsequently degraded under physiological conditions; meanwhile, under oxidative stress or with increased an ABA level, OsABI5 was released from the complex, phosphorylated, and transactivated the ABA response genes. Therefore, OsKEAP1–OsABI5 bore some resemblance to KEAP1–NRF2 in terms of its function and working mechanism.